The Modern Dance : Seven Statements of Belief - Hawkins, Erick; Cohen, Selma Jeanne, 1920-2005 (Book collections on Project MUSE., 2011)
Seven statements of belief by Jose Limón, Anna Sokolow, Erick Hawkins, Donald McKayle, Alwin Nikolais, Pauline Koner, and Paul Taylor.